The Genus Aspergillus - Pathogenicity, Mycotoxin Production and Industrial Applications 2022
DOI: 10.5772/intechopen.98897
|View full text |Cite
|
Sign up to set email alerts
|

Mycovirus Containing Aspergillus flavus and Acute Lymphoblastic Leukemia: Carcinogenesis beyond Mycotoxin Production

Abstract: Carcinogenic effects of Aspergillus spp. have been well established and generally attributed to a variety of mycotoxin productions, particularly aflatoxins. It is known that most carcinogenic mycotoxins, with the exception of fumonisins, are genotoxic and mutagenic, causing chromosomal aberrations, micronuclei, DNA single-strand breaks, sister chromatid exchange, unscheduled DNA synthesis etc. Some Aspergillus spp. are infected with mycoviruses which can result in loss of aflatoxin production. The effects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Given the commonalities between known oncogenes and viral-targeted cellular pathways, it is not surprising that some mammalian viruses can cause cancer by circumventing or hijacking cell death modalities. Interestingly, a recent study discovered that plasma from lymphoblastic leukemia (ALL) patients, was reactive with supernatants from a mycovirus-containing Aspergillus flavus isolate, while sera from healthy controls were non-reactive, suggesting mycovirus-mediated leukemogenesis in this group of patients ( Tebbi et al., 2021 ). The question arises, whether mycoviruses may impact human or animal health directly or once internalized using the fungal cell as a carrier.…”
Section: Mycoviruses: Backseat Drivers Of Fungal Diseasementioning
confidence: 99%
“…Given the commonalities between known oncogenes and viral-targeted cellular pathways, it is not surprising that some mammalian viruses can cause cancer by circumventing or hijacking cell death modalities. Interestingly, a recent study discovered that plasma from lymphoblastic leukemia (ALL) patients, was reactive with supernatants from a mycovirus-containing Aspergillus flavus isolate, while sera from healthy controls were non-reactive, suggesting mycovirus-mediated leukemogenesis in this group of patients ( Tebbi et al., 2021 ). The question arises, whether mycoviruses may impact human or animal health directly or once internalized using the fungal cell as a carrier.…”
Section: Mycoviruses: Backseat Drivers Of Fungal Diseasementioning
confidence: 99%
“…Several studies have correlated the possible involvement and association of fungal species, particularly Candida , with the development and progression of various types of cancer. While most attention has been directed to yeasts in the so-called blastomycete theory of cancer, more recently, other mechanisms, including the possible role of mycoviruses in fungal organisms, have been suggested [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. In the recent past, it has been shown that the in vitro exposure of mononuclear cells from individuals who have a history of acute lymphoblastic leukemia (ALL) and are in full remission, without any evidence of the disease, including long-term survivors, to a certain mycovirus-containing Aspergillus flavus (MCAF) results in the re-development of cell surface phenotypes and genetic markers characteristic of active ALL [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…If this is due to the certain genetic or epigenetic background in the ALL patients is not clear. In a related study, unlike controls, patients with ALL were found to have antibodies for the products of MCAF [ 92 ]. It is of interest that the mycovirus-containing Aspergillus flavus used for these studies was isolated from the home of a patient with ALL and the organism did not produce any aflatoxin [ 91 , 92 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations